(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2023)
his article questions the existence of a human right to water in the African human rights system. The doctrinal analysis reveals that at the regional level, treaties only indirectly contribute to the recognition of a human right to water, whereas thelatter is clearly enshrined in certain texts in force at the sub-regional level. These provide a legal basis distinct from that of other human rights. The case-law analysis underscores the missed opportunities for the regional judge to enshrine this humanright to guarantee its real protection by the states. Nonetheless, the article highlights the contribution of the African Commission on Human and Peoples’ Rights’ soft law to the explicit consecration of a human right to water and the various state obligations that ensue to ensure its effectiveness. This constitutes a significant progress in the protection of human rights. The author proposes that monitoring bodies can refer to this soft law to enshrine a human right to water in the subsequent development of their jurisprudence as it can serve as a compass to stimulate and guide domestic legal reforms aimed at a genuine guarantee of this right.